Nonlinear dynamic behaviour of framed structures subjected to ground motions - Zhao, Dianfeng. (2008)
The research work presented in this thesis proposes an approach, with the specific formulation of characteristic matrices, to analyze the nonlinear dynamics behavior of steel frames subjected to ground motions. The analysis is based on the displacement and energy framework, and the ground motions under consideration are induced by earthquake as well as underground shock. The ultimate aim is to implement a complete, realistically accurate and possibly efficient algorithm to investigate the insights of steel frame.